TEACHER’S PROVIDING DIRECT ORAL FEEDBACK ON STUDENTS’ PRONUNCIATION OF READING ALOUD AND STUDENTS’ RESPONSES - Ahlan; Fatikhatur Rizqya; Mohammad Ilham Yasin (EDUCATUM: Scientific Journal of Education, 2026)
This study investigates the role of teacher feedback in improving students’ pronunciation during English reading activities and explores students' responses to the feedback provided. Conducted as a qualitative case study, the research involved classroom observation and student interviews in an English for Specific Purposes (ESP) context at the Islamic Economic Law Department. The findings revealed that students frequently mispronounced common English words due to a reliance on spelling rather than pronunciation rules. Corrective feedback from the teacher, delivered immediately after each student’s reading, helped students identify and correct their errors. The majority of students responded positively, showing increased motivation, attentiveness, and willingness to prepare for future reading sessions. These findings support the idea that timely, specific, and supportive feedback plays a significant role in enhancing students’ reading accuracy and engagement. The study contributes to the ongoing discussion about effective feedback strategies in EFL classrooms and suggests that oral corrective feedback is a valuable tool in teaching English pronunciation.